FALASTIN OZODLIK TASHKILOTI VA UNING FAOLIYATI - Pardayev Bekzod Shokirovich, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This article contains a historical analysis of the establishment of the Palestine Liberation Organization, its struggle processes, the role of the organization in the history of Palestine, relations with Israel, and the escalation of relations between Jordan and Palestine. The article also provides detailed information about the 1993 Oslo Agreement.